Water quality variation in the middle route of South-to-North Water Diversion Project, China - Wang, Yuanzhu; Wang, Chenglin; Zhang, Chunmei; Liang, Jiangkui; Mi, Wujuan; Song, Gaofei; Zhu, Yuxuan; Wang, Shulei; Shang, Yuming; Bi, Yonghong (Frontiers in Environmental Science, 2023)
The Middle Route of South to North Water Diversion Project (MRP) is the longest inter-basin water diversion project with the largest beneficial population, its water quality has attracted much attention. Seasonal investigation on eleven sampling sites along the MRP from 2018 to 2019 was conducted in this study, water temperature (WT), pH, turbidity, transparency, CODMn, dissolved oxygen (DO), total phosphorus (TP), phosphate (PO4-P), total nitrogen (TN), ammonia (NH4-N), nitrate (NO3-N), Chlorophyll a (Chl a), was determined synchronously. Single leakage distance clustering analysis identified the spatio-seasonal heterogeneity of physiochemical parameters. Trophic level index (TLI) and water quality status (WQI) were assessed, TLI increased and WQI decreased from south to north; TLI and WQI had significantly seasonal differences (P < 0.001), the best water quality appeared in autumn, and the lowest TLI was in winter. The trophic level was ‘oligotropher to mesotropher’; water quality status was ‘good’ in the MRP. The multiple linear stepwise regression analysis confirmed that TN, Chl a and CODMn were the driving factors on water quality. These factors were applied to build the simplified WQI model (WQImin model), which was confirmed as a reliable method of water quality assessment for the MRP instead of TLI and WQI. The results provided support for water quality evaluation of the MRP.